2017
DOI: 10.1038/s41598-017-05692-4
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis and Optoelectronic Properties of Supramolecular Assemblies of Chiral Perylene Diimides in a Binary Solvent System

Abstract: Chiral supramolecular structures are attracting great attention due to their specific properties and high potential in chiral sensing and separation. Herein, supramolecular assembling behaviors of chiral perylene diimides have been systematically investigated in a mixed solution of tetrahydrofuran and water. They exhibit remarkably different morphologies and chiral aggregation behaviors depending on the mixing ratio of the solvents, i.e., the fraction of water. The morphogenesis and optoelectronic properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 39 publications
0
42
0
Order By: Relevance
“…Chirality and its expression through circular dichroism (CD) are also properties that can be linked to aggregate structure. [125][126][127] Tetraphenylethylene (TPE) is one of the most studied AIEgens and its isolated molecules are achiral because of the free rotation of the four phenyl rings, as reflected by the silent CD signal of its solution. [128][129][130] However, in 2011, Zhang et al observed a pair of inverse CD spectra from two TPE crystals ( Figure 5).…”
Section: Static Aggregatesmentioning
confidence: 99%
“…Chirality and its expression through circular dichroism (CD) are also properties that can be linked to aggregate structure. [125][126][127] Tetraphenylethylene (TPE) is one of the most studied AIEgens and its isolated molecules are achiral because of the free rotation of the four phenyl rings, as reflected by the silent CD signal of its solution. [128][129][130] However, in 2011, Zhang et al observed a pair of inverse CD spectra from two TPE crystals ( Figure 5).…”
Section: Static Aggregatesmentioning
confidence: 99%
“…Recently, supramolecular chirality has attracted great attention due to its promising applications in chiral recognition, sensing, and catalysis 1 . Several optical devices based on the supramolecular chirality and other biological applications have also been reported 1 , 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Organic p-conjugated materials have received much attention due to their tunable optical and electrical properties, suitability for exible device fabrication, and large-area processability. [1][2][3] Organic eld-effect transistors (OFETs), 4,5 organic light-emitting diodes (OLEDs), 6 organic phototransistors (OPTs), [7][8][9] organic photovoltaics (OPVs), 10,11 organic memories, 12 and organic sensors 13 have been successfully developed. Phototransistors, which allow one to control channel conductance via light absorption, are particularly applicable to electronic devices such as light sensors and optical switches.…”
Section: Introductionmentioning
confidence: 99%